Living with COPD: understanding patient experiences through the lens of photovoice - Sumner, Jennifer; Bundele, Anjali; Shankar, Ravi; Chong, Lin Siew; Kowitlawakul, Yanika; Mukhopadhyay, Amartya (BMC pulmonary medicine, 2023)
Background Conventional quantitative or qualitative methodologies may not encompass the wide array of experiences of individuals living with Chronic Obstructive Pulmonary Disease (COPD). We used a novel approach – photovoice—to understand the impact of COPD on activities of daily living (ADLs) in a multicultural Asian country. Methods We recruited a purposive sample of eight patients from the outpatient clinics of the National University Health System, Singapore, between December 2020 and August 2021. We adopted a photovoice approach for data collection; participants were invited to take photos of how ADLs were impacted by COPD and attend a follow-up interview. An Interpretative Phenomenological Analysis method was used to analyze the data. Data saturation was reached by the seventh patient. Results COPD and the resulting breathlessness had a profound and diverse impact on our participants’ lives. Living with COPD required substantial changes to how everyday tasks are performed, and participants learnt new strategies to deal with such tasks. A mixture of active and passive coping styles was evident. Feelings of frustration, anxiety and a sense of isolation were also reported. Contextual factors impacting ADLs included challenging climatic conditions and the local popularity of traditional or alternative medicine. Conclusion The photovoice technique improved our understanding of the lived experiences of COPD patients and can benefit those who struggle to articulate their views by offering a different way to communicate beyond conventional interviewing.